Synthesis of rice straw extracted nano-silica-composite membrane for CO2 separation. (10th June 2018) - Bhattacharya, Madhubanti; Mandal, Mrinal Kanti
Abstract: The attractive feature of this work lies in utilizing biological waste by-product nano-silica extracted from rice straw (ligno-cellulosic biomass) as filler to synthesize nano-composite polymeric membrane comprising polyether-polyamide block co-polymer (PEBA) to improve performances for CO2 separation from its streams. The gravimetric method was used to isolate bio-nano-silica from black liquor (de-lignified solution of ligno-cellulosic biomass) having surface area (BET), pore volume (BJH) and average diameter as 404.3 m 2 /g, 0.571 cm 3 /g and 14.8 nm respectively. Morphological behaviour of bio-nano-silica was examined using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS). The nano-particle embedded PEBA composite membranes were synthesized by solution casting method at different silica concentrations (i.e., 0.5, 1 and 2 wt%). Good dispersion, adhesion of the fillers, structural modification and surface roughness within the polymer matrix were confirmed by the field emission scanning electron microscopy (FESEM) images, atomic force microscopy (AFM), fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) analysis. Several permeation experiments were conducted by varying feed pressure (i.e., 3–7 kg/cm 2 ), temperature (i.e., 30–50 °C) and concentrations of silica in membrane matrix for pure gases (CO2 /CH4 /Air). The results unveiled substantial improvement in permeability of CO2 (from 22.0 to 270.0 Barrer) at highest concentration of silica (2 wt%) and enhancement with different rate of ideal selectivities for CO2 /CH4 (5.2–5.3) and CO2 /Air (1.7–4.1) in comparison to pristine PEBA membrane at 7 kg/cm 2 pressure and 30 °C temperature. It was duly noted that the trend of permeability for pure gases for both pressure and temperature variation is in the order of CO2 >Air > CH4 . The Robeson's upper bound diagram confirmed the progressive outcome in aspect of both permeability and selectivity. Graphical abstract: Image Highlights: Extraction of nano-silica from biological waste-rice straw. Utilization of wasted bio-nano-silica for nano-composite membrane preparation. Synthesis of blended membrane using inorganic nano-silica filler. Role of bio-nano-silica for CO2 separation.